Depressive symptoms and its associated factors among secondary school adolescents of Birtamod Municipality, Jhapa, Nepal. - Rachana Giri; Santosh Khadka; Anisha Chalise; Kshitiz Swar; Shishir Paudel (Public Library of Science (PLoS), 2024)
Depression is a rising public health concern affecting adolescents' mental health throughout the world. This cross-sectional study aimed to assess the prevalence of depressive symptoms and its associated factors among adolescents from urban Nepal. The depressive symptoms among 271 randomly selected secondary school adolescents of Britamod Municipality were assessed using Center for Epidemiologic Studies Depression Scale (CES-D). The chi-square test and multivariable logistic regression were executed to assess the statistical relationship between potential risk factors and depressive symptoms at 5% level of significance. The prevalence of depressive symptoms was 42.8% (95% CI: 37.3-49.1%). Multiple logistic regression revealed that female adolescents (aOR: 2.309, 95% CI: 1.233-4.325), adolescents enrolled in higher grades i.e. 10th grade (aOR: 4.576, 95% CI: 1.482-9.128), studying at private school (aOR: 2.302, 95% CI: 1.184-4.476), not sharing their problems with their friends (aOR: 3.022, 95% CI: 1.477-6.186), presence of perceived academic stress (aOR: 2.388, 95% CI: 1.263-4.518), dissatisfaction with current academic performance (aOR: 2.278, 95% CI: 1.141-4.518), lower perceived family support (aOR: 3.440, 95% CI: 1.276-9.275), and lower self-esteem (aOR: 2.139, 95% CI: 1.061-8.708) had higher odds of experiencing depressive symptoms. There is a high prevalence of depression among Nepalese adolescents. The findings highlight the need for health promotion interventions focusing on mental health awareness, enhancing social support systems, and implementing stress reduction strategies within schools to mitigate the burden of depression among Nepalese adolescents.